1986
DOI: 10.2466/pr0.1986.59.3.1043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Burnout among Professional Psychologists to Professional Expectations and Social Support

Abstract: The current study investigated the phenomenon of professional burnout among psychologists of varying experience. Self-report measures were employed in a mail survey of Ontario psychologists. The average level of burnout, as assessed by the Tedium measure, was i n the low moderate range ( M of 3.0 on a 7-point scale). Of the total sample of 255 subjects, 6.3% were determined to be burned out. Burnout was not related to experience in the profession or to other demographic variables but was significantly related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 12 publications
3
31
1
1
Order By: Relevance
“…Preliminary evidence found high burnout was associated with coping by excessively dwelling on one's emotions (emotion‐focused) or avoiding one's emotions (avoidant‐coping) (Ackerley et al., ; Cushway & Tyler, ; Huebner, ; Wilkerson, & Bellini, ), potentially due to reduced opportunities for interpersonal connection and social support (Huebner, ). There were mixed findings on the role of social support, but the majority of studies identified that social support alongside personal therapy, was correlated with high burnout among psychotherapists (Darongkamas et al., ; Kahill, ; Ross et al., ; Stevanovic, & Rupert, ), although it is probable that they were accessing personal therapy as a consequence of (rather than predictor of) burnout (Darongkamas et al., ; Di Benedetto & Swadling, ; Kovach Clark, Murdock, & Koetting, ). A study by Rzeszutek and Schier () posited that perceptions of social support were stronger predictors of burnout than actual social support itself, whereby social support may only be protective if the psychotherapist feels supported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary evidence found high burnout was associated with coping by excessively dwelling on one's emotions (emotion‐focused) or avoiding one's emotions (avoidant‐coping) (Ackerley et al., ; Cushway & Tyler, ; Huebner, ; Wilkerson, & Bellini, ), potentially due to reduced opportunities for interpersonal connection and social support (Huebner, ). There were mixed findings on the role of social support, but the majority of studies identified that social support alongside personal therapy, was correlated with high burnout among psychotherapists (Darongkamas et al., ; Kahill, ; Ross et al., ; Stevanovic, & Rupert, ), although it is probable that they were accessing personal therapy as a consequence of (rather than predictor of) burnout (Darongkamas et al., ; Di Benedetto & Swadling, ; Kovach Clark, Murdock, & Koetting, ). A study by Rzeszutek and Schier () posited that perceptions of social support were stronger predictors of burnout than actual social support itself, whereby social support may only be protective if the psychotherapist feels supported.…”
Section: Discussionmentioning
confidence: 99%
“…psychotherapists (Darongkamas et al, 1994;Kahill, 1986;Ross et al, 1989;), although it is probable that they were accessing personal therapy as a consequence of (rather than predictor of) burnout (Darongkamas et al, 1994;Di Benedetto & Swadling, 2014;Kovach Clark, Murdock, & Koetting, 2009). A study by Rzeszutek and Schier (2014) posited that perceptions of social support were stronger predictors of burnout than actual social support itself, whereby social support may only be protective if the psychotherapist feels supported.…”
Section: Coping Mechanisms and Social Supportmentioning
confidence: 99%
“…(35) Additionally, burnout is associated with increased alcohol and substance abuse and impaired interpersonal relationships. (6) Given the potential impact of burnout on the quality patient care, burnout may have medicolegal and financial implications for surgeons and the institutions at which they work.…”
Section: Introductionmentioning
confidence: 99%
“…Maslach and Jackson (1982) later operationalized the concept into a three‐part construct that included emotional exhaustion, depersonalization, and a reduced sense of personal accomplishment. Although exact figures are unknown, it is estimated that approximately 10–15% of practicing mental health professionals will succumb to burnout during the course of their careers (Kahill, 1986). Burnout is problematic for therapists in that it contributes to lower morale, reduced self‐esteem, a tendency to dehumanize clients, and, ultimately, to leaving the field completely (Baird & Jenkins, 2003).…”
mentioning
confidence: 99%